Angel Núñez: La obra narrativa de Roberto Arlt, (Buenos Aires), Minor Nova 1968. 98 p. 18 x 11,5 cm. - Ruiz Díaz, Adolfo F. (1969)
Fil: Ruiz Díaz, Adolfo F.. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras